Analisis Perbandingan Efisiensi dan Biaya Penggunaan Lampu AC dan DC Menggunakan PLTS - Alfathina, Ghina; Irianto, chairul Gagarin; kasim, ishak; Abduh, Syamsir; sari, tyas kartika (Website, 2023)
Abstract Solar power plant is one of the developments in the use of renewable energy that has received government support through Ministerial Regulation No.49 of 2018 and Ministerial Regulation No.26 of 2021 regarding rooftop solar power plant. Based on the 2019 solar power plant roadmap draft, the investment cost of rooftop solar power plant per kWp is around 14-25 million rupiah, the amount of this investment is an important consideration for the community to install rooftop solar power plant. One alternative to reduce the investment cost of rooftop solar power plant is to reduce the capacity of the inverter by using lighting from DC lamps. This research was conducted by comparing the efficiency values and investment costs, and using the benefit-cost analysis method to compare a series of relevant costs and benefits between the use of DC lamps and AC lamps for household lighting using PLTS. The results of this research is that DC lamps have a light current of 280 – 350 lumens, an illumination intensity of 48 lux, and a PLTS system efficiency of 98,5% which is higher in value compared to AC lamps which have a light current of 250 lumens, an illumination intensity of 21 lux, and a PLTS system efficiency of 49,3% with the same lamp power of 3W. Analysis of the investment feasibility of on-grid and off-grid PLTS, both 2200VA and 900VA shows that the NPV is negative and the BCR value is less than 1, so the investment is not yet feasible. Keywords: Investment feasibility analysis, DC Lamps, AC Lamps, Solar Rooftop